Behaviors of two semi-passive oscillating hydrofoils with a tandem configuration. (1st January 2021) - Ma, Penglei; Wang, Yong; Xie, Yudong; Liu, Guijie
Abstract: Two hydrofoils with a tandem spatial configuration can share the same flow window. The wake vortex interaction and blockage effect have noticeable impacts on the response of two hydrofoils for a semi-passive system. In this study, the responses of two oscillating hydrofoils with a tandem arrangement are examined using a numerical approach. The results indicate that the downstream hydrofoil has an inferior energy harvesting performance because it operates in the upstream hydrofoil wake. Several special cases were observed. As a result of a negative interaction in the wake vortices, (i) two hydrofoils were shown to have different heaving equilibrium positions and thus no longer share the flow window; and (ii) the downstream hydrofoil was demonstrated to have a larger heaving amplitude but a lower energy harvesting performance. At a very high oscillation frequency, the downstream hydrofoil tends to incur an irregular response owing to the intense vortex formation and shedding, as well as a constant interaction of the wake vortices. The downstream hydrofoil achieves an unexpectedly better energy harvesting performance due to a favorable interaction of the wake vortices. However, the entire system can't achieve high efficiency due to the poor energy harvesting performance of the upstream hydrofoil. When two semi-passive oscillating hydrofoils have a tandem configuration, negative wake vortex interactions should be avoided instead of seeking a favorable interaction. Highlights: The response of two semi-passive oscillating hydrofoils with a tandem configuration was discussed. The heaving amplitude of the downstream hydrofoil tends to be lower than that of the upstream hydrofoil. Two hydrofoils may not share the same flow window due to negative wake vortex interactions. The favorable wake vortex interaction does not mean that the entire system has ideal energy harvesting performance. For tandem semi-passive systems, negative vortex interaction should be avoided instead of seeking favorable interactions.